Knowledge Management Orientation And Business Performance: The Mediating Roles Of Service Quality And Relationship Quality - Abdul Rahman, Baharom (2008)
This study proposes Service Quality and Relationship Quality as mediators that, if properly undertaken, would reflect an aspect of the organization's performance, which, in the end, improved business performance. This document explains the research model and its empirical testing in a sample from the manufacturing and service industries in Malaysia.